Market concentration in agricultural industries - Goodwin, Barry K.; Glauber, Joseph W. (American Enterprise Institute, 2026)
Mergers and acquisitions in agricultural input industries have led to high levels of concentration such that a small number of firms account for most sales. We examine the concentration in seed, fertilizer, and livestock markets. Policymakers have raised concerns that such concentration may worsen consumers’ and farmers’ welfare. Agricultural market concentration might increase market power, but it might also result from economies of scale, in which case aggregate welfare may improve. The ongoing debate over tariffs has complicated the situation since higher tariffs, as well as antidumping and countervailing duties, might increase input costs for farmers.